2011
DOI: 10.1007/s11670-011-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of plasma MicroRNA-21 is associated with chemotherapeutic response in patients with non-small cell lung cancer

Abstract: Objective: To examine plasma microRNA-21 (miR-21) level in patients with non-small cell lung cancer (NSCLC) and its potential correlation with chemotherapeutic response.Methods: 77 NSCLC patients and 36 age and sex-matched healthy controls were included. Plasma miR-21 concentration was examined using a quantitative real-time reverse transcription polymerase chain reaction assay (qRT-PCR). Potential correlation between plasma mir-21 concentrations with chemotherapeutic responses was analyzed in 35 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…After full‐text reading by two reviewers, 39 failed to meet the inclusion criteria. Finally, 28 records were included in the meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…After full‐text reading by two reviewers, 39 failed to meet the inclusion criteria. Finally, 28 records were included in the meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Most studies selected miRNAs by microarray [ 12 , 13 , 18 , 21 , 22 , 24 , 26 28 , 34 37 , 39 , 41 , 42 , 46 49 , 52 , 55 , 59 , 61 , 64 , 67 , 74 ]. Some identified miRNAs by literature [ 11 , 14 – 16 , 19 , 23 , 25 , 29 33 , 40 , 43 45 , 50 , 51 , 53 , 54 , 56 58 , 60 , 62 , 63 , 65 , 66 , 68 – 73 , 75 , 84 ]. To give an insight to future studies, we listed the potential miRNAs reported by literature that could serve as circulating biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that dysregulation of miRNA expression contributes to the development and progression of cancer (26)(27)(28). miRNA profiles can also be used as biomarkers for detection of cancer (29)(30)(31)(32)(33)(34) and to predict chemotherapeutic response (35)(36)(37)(38). It is therefore of particular interest to investigate the therapeutic application of miRNAs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%